Obstructive Sleep Apnea- A Comprehensive Review of Risk Factors, Pathogenesis and Management - Noura Homood Saeed Alshahrani; Monerah Mohammed Ayed Alqahtani; Ghada Hassan Abdullah Alshahrani; Muhammad Abdullah kamran (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2021)
Sleep is a blessing to humans. Good quality of sleep helps people to live and enjoy their lives. Obstructive sleep apnea is a common sleep disorder accompanied by the onset of sleep, apnea or hypopnea , choking sensation and loud snoring. Chronic obstructive sleep apnea may leads to systemic side effects especially on cardiovascular system and other vital body organs. Although exact etiology is unknown, various factors may contribute to the development of obstructive sleep apnea. The diagnosis is made by multiple methods. treatment is also multimodality depends on the type and severity. This review article is written in order to provide an insight to the risk factors, pathogenesis, and management of obstructive sleep apnea. Especial emphasis is made on the dentist's role, duties, and responsibilities in the diagnosis and management of obstructive sleep apnea.